PENGARUH PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS 5 SDN 19 BANDA ACEH - Raudhatul Ismi; Regina Rahmi; Raziska Ibrahimi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model on students’ learning outcomes in the IPAS subject for fifth-grade students at SDN 19 Banda Aceh. The background of this study is based on the low learning outcomes of students caused by teacher-centered learning methods, resulting in low student participation and engagement in the learning process. This research employed a quantitative approach with a pre-experimental design using the One Group Pretest-Posttest Design. The population as well as the sample consisted of all 30 fifth-grade students of SDN 19 Banda Aceh. Data were collected through tests, namely pretest and posttest. The data were analyzed using normality test, N-Gain test, and hypothesis testing (paired sample t-test). The results showed that the data were normally distributed based on the Shapiro-Wilk test, with a significance value of 0.075 for the pretest and 0.082 for the posttest (>0.05). The N-Gain test result indicated an average score of 0.5474, which falls into the medium category, showing an improvement in students’ learning outcomes. Furthermore, the hypothesis test showed a significance value of 0.000 (<0.05), indicating a significant difference between pretest and posttest results. Therefore, it can be concluded that the implementation of the Problem Based Learning model has a significant effect on improving students’ learning outcomes in the IPAS subject for fifth-grade students at SDN 19 Banda Aceh